Rheology of concentrated crystal suspensions: sucrose fondants as hard particles in soft matter - Hartge, Hannah M.; Flöter, Eckhard; Vilgis, Thomas A. (Frontiers in Soft Matter, 2025)
Hard particle dispersions are abundant in food as well as technical applications. In particular, the production of many candies like fondants, crystalline sugars or creamed honeys involves agitation of concentrated suspensions of microscopic crystals in saturated solutions. However, the complex rheological behavior of such non-colloidal suspensions with poly-disperse, irregular particles is not fully understood. This work investigates different sucrose suspensions with a particle volume fraction of about 50%. After detailed image analysis of the varying particle size distributions and shapes, the flow properties are investigated by oscillatory rheology. Amplitude sweeps, frequency sweeps and thixotropy tests show the dependency of rheological behavior on the microstructure of the suspensions. In particular, all samples show characteristic strain softening with subsequent strain hardening that indicates jamming at large strains. This is observed irrespective of specifics in the particle shape and material, suggesting universal behavior due to the high particle volume fraction. They also show significant time-dependent behavior. However, sedimentation rates are higher and structure rebuilding is lower for larger particle sizes and dispersity. The observed strain softening and structure rebuilding are explained by rearrangement of the crystals: Under moderate strain amplitudes, friction and collisions are minimized, with a larger optimization potential for larger dispersities. When oscillations are reduced again, mainly small particles re-arrange in an arbitrary order over time, leading to an increase in loss and storage modulus and thus thixotropic behavior. This time-dependent process needs to be taken into account when measuring or processing concentrated crystal suspensions. Our findings contribute to a better understanding of concentrated suspensions simple in composition, but complex in their flow properties. The observed behavior strongly depends on the particle-particle interactions. Thus, our findings can be transferred to other areas involving concentrated, non-Brownian frictional suspensions of compact hard particles, as they are often found in food, technical applications or geology.